Dinamika Locus of Control terhadap Kematangan Karier pada Siswa Sekolah Menengah - Dwi Septia Ningsih; Risma Anita Puriani (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2026)
This study aims to examine the dynamics of locus of control on the career maturity of high school students. The study uses a literature review method with a traditional review approach through searching and critically reviewing relevant research articles. Data were obtained from publications published between 2020 and 2025 with the keywords “locus of control” and “career maturity.” Based on the criteria set, 15 articles were obtained that examined locus of control and career maturity in junior high school, high school, and vocational high school students. The results of the study show that locus of control is correlated with the career maturity of secondary school students, where an internal locus of control orientation tends to be associated with a higher level of career readiness, while an external orientation is associated with low career planning and decision-making skills. These findings confirm the role of locus of control as a psychological factor that influences the career maturity of secondary school students.